Hubungan Obesitas Sentral Terhadap Lipid Profil Pada Peserta Medical Check Up di Niki Diagnostik Center Denpasar - Daryaswanti, Putu Intan; Adiatmika, I Putu Gede; Bagiartha, I Made Oka (Jurnal Kesehatan Medika Udayana, 2017)
ABSTRACT Background: Central obesity is the fat deposition in the abdominal area and can cause adverse health effect. Dyslipidemia is a condition that follows the obese, where there is a lipid metabolism disorder characterized by changes in plasma lipid fractions (hypercholesterolemia, hypertriglyceridemia, increased LDL cholesterol and decrease HDL cholesterol). The situation is a high risk factor for atherosclerosis. This study aims to determine the relationship between central obesity and lipid profiles. Methods:The study was conducted at the check-up participants who have waist circumference ≥ 80 cm for women and waist circumference ≥ 90 cm for men. The study design was analytical descriptive cross-sectional study. Results: Data of waist circumference were measured by anthropometric assessment and data of lipid profiles were measured by using a TRX 7010. The results showed that waist circumference of participants were 91-115 cm, and all participants had increased levels of lipid profile. Based on the Pearson correlation test, a score is significant correlation between central obesity on LDL (p <0.05), and there is no significant correlation among to the total cholesterol, HDL cholesterol and triglycerides (p> 0.05). Conclusions:  It was concluded there is a relationship between central obesity and LDL cholesterol and no relationship among central obesity, total cholesterol, HDL cholesterol, and triglycerides. ABSTRAK Latar belakang: Obesitas sentral merupakan timbunan lemak yang terdapat di daerah perut dan dapat menimbulkan dampak buruk pada kesehatan. Dislipidemia adalah kondisi yang mengikuti obesitas, dimana terjadi gangguan metabolisme lipid yang ditandai dengan perubahan fraksi lipid plasma (hiperkolesterolemia, hipertrigliseridemia, peningkatan kolesterol LDL dan penurunan kolesterol HDL). Keadaan tersebut merupakan faktor risiko tinggi terjadinya aterosklerosis. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara obesitas sentral dan lipid profil. Metode: Penelitian dilakukan pada peserta check up dengan lingkar pinggang ≥ 80 cm untuk perempuan dan lingkar pinggang ≥ 90 cm untuk laki-laki. Rancangan penelitian adalah deskriptif analitik cross-sectional study. Data lingkar pinggang diukur dengan pemeriksaan antopometri dan data lipid profil diukur dengan menggunakan alat TRX 7010. Hasil: penelitian didapatkan ukuran lingkar pinggang peserta adalah 91-115 cm dan semua peserta mengalami peningkatan kadar lipid profil. Berdasarkan uji korelasi Pearson, didapatkan nilai hubungan bermakna antara obesitas sentral terhadap LDL (p<0,05), dan tidak ada hubungan bermakna pada kolesterol total, kolesterol HDL dan trigliserida (p>0,05). Simpulan: ada hubungan antara obesitas sentral dengan kolesterol LDL dan tidak ada hubungan antara obesitas sentral, kolesterol total, kolesterol HDL, dan trigliserida.